Prostate cancer and bone metabolism: new horizons - Di Francesco, Simona; Tenaglia, Raffaele L. (Progress in Nutrition, 2014)
The reciprocal relationship between bone metabolism and prostate cancer remains heated debate. In this review we analyzed the mutual relationship between bone tissue and prostate cancer, highlighting in particular as the tumor cells themselves can produce specific proteins able to directly influence the bone metabolic activity